If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + y) * dx + (x + y + -2) * dy = 0 Reorder the terms for easier multiplication: dx(x + y) + (x + y + -2) * dy = 0 (x * dx + y * dx) + (x + y + -2) * dy = 0 Reorder the terms: (dxy + dx2) + (x + y + -2) * dy = 0 (dxy + dx2) + (x + y + -2) * dy = 0 Reorder the terms: dxy + dx2 + (-2 + x + y) * dy = 0 Reorder the terms for easier multiplication: dxy + dx2 + dy(-2 + x + y) = 0 dxy + dx2 + (-2 * dy + x * dy + y * dy) = 0 Reorder the terms: dxy + dx2 + (dxy + -2dy + dy2) = 0 dxy + dx2 + (dxy + -2dy + dy2) = 0 Reorder the terms: dxy + dxy + dx2 + -2dy + dy2 = 0 Combine like terms: dxy + dxy = 2dxy 2dxy + dx2 + -2dy + dy2 = 0 Solving 2dxy + dx2 + -2dy + dy2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'd'. d(2xy + x2 + -2y + y2) = 0Subproblem 1
Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0Subproblem 2
Set the factor '(2xy + x2 + -2y + y2)' equal to zero and attempt to solve: Simplifying 2xy + x2 + -2y + y2 = 0 Solving 2xy + x2 + -2y + y2 = 0 Move all terms containing d to the left, all other terms to the right. Add '-2xy' to each side of the equation. 2xy + x2 + -2y + -2xy + y2 = 0 + -2xy Reorder the terms: 2xy + -2xy + x2 + -2y + y2 = 0 + -2xy Combine like terms: 2xy + -2xy = 0 0 + x2 + -2y + y2 = 0 + -2xy x2 + -2y + y2 = 0 + -2xy Remove the zero: x2 + -2y + y2 = -2xy Add '-1x2' to each side of the equation. x2 + -2y + -1x2 + y2 = -2xy + -1x2 Reorder the terms: x2 + -1x2 + -2y + y2 = -2xy + -1x2 Combine like terms: x2 + -1x2 = 0 0 + -2y + y2 = -2xy + -1x2 -2y + y2 = -2xy + -1x2 Add '2y' to each side of the equation. -2y + 2y + y2 = -2xy + -1x2 + 2y Combine like terms: -2y + 2y = 0 0 + y2 = -2xy + -1x2 + 2y y2 = -2xy + -1x2 + 2y Add '-1y2' to each side of the equation. y2 + -1y2 = -2xy + -1x2 + 2y + -1y2 Combine like terms: y2 + -1y2 = 0 0 = -2xy + -1x2 + 2y + -1y2 Simplifying 0 = -2xy + -1x2 + 2y + -1y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
d = {0}
| 100=4z-20 | | 100=4z-10 | | 1-m-6=6m | | 1/6x=-12 | | 46-3n=-26 | | 2x-3/8-x-2/6 | | 38k+7k=8(k+4) | | 8x^2+7x+6=0 | | 4x-w=vx+y | | 15=17x+5-5x | | 5+3c+4c= | | 14=9x+2-6 | | 1=3u-5 | | 16x^3+250=0 | | 1/2(2x-6)=4(1/4x-3/4) | | 28y+8=16 | | 6x+29=13-48 | | -7x+8+-4+-9= | | 20*log(x)=55 | | 2.00+1.50=54.5 | | -3(4v-9)+7v=4(v+6) | | 20log(x)=55 | | 2(12p+16)= | | 6=-4.1+r | | x+.06x=400 | | 268+3*g=654 | | -25.8=43v | | 268+3*g=900 | | h=15t-4.9t^2+2 | | c+4.3=-6.7 | | 5x+1=-5x-1 | | (Dy/dx)=3e^5 |